Current directions for improving the administrative, legal and organisational principles of the activities of higher education institutions of the MIA of Ukraine which provide police training, taking into account the requirements of martial law - K. L. Buhaichuk; O. A. Morhunov (Bulletin of Kharkiv National University of Internal Affairs)
The authors have studied the legal and organisational framework for the activities of higher education institutions of the Ministry of Internal Affairs of Ukraine which provide police training. It has been determined that the state of war caused by Russia’s aggression against Ukraine imposes new requirements on the quality of staffing of all security and defence sector entities, in particular, the National Police of Ukraine. Today, police units take part in hostilities, are involved in stabilization and filtration measures, mine countermeasures, evacuation of the civilian population from the combat zone and adjacent territories. Policemen are also involved in providing assistance to the population in the liberated territories, delivering food and essential items to people who have survived the occupation in extremely difficult conditions.